Development of the European Ladybirds Smartphone Application: A Tool for Citizen Science - Skuhrovec, Jiří; Roy, Helen E.; Brown, Peter M. J.; Kazlauskis, Karolis; Inghilesi, Alberto F.; Soares, Antonio O.; Adriaens, Tim; Roy, David B.; Nedvěd, Oldřich; Zach, Peter; Viglášová, Sandra; Kulfan, Ján; et al. (Frontiers in Ecology and Evolution, 2021)
Wildlife observations submitted by volunteers through citizen science initiatives are increasingly used within research and policy. Ladybirds are popular and charismatic insects, with most species being relatively easy to identify from photographs. Therefore, they are considered an appropriate taxonomic group for engaging people through citizen science initiatives to contribute long-term and large-scale datasets for use in many different contexts. Building on the strengths of a mass participation citizen science survey on ladybirds in the UK, we have developed a mobile application for ladybird recording and identification across Europe. The main aims of the application are to: 1. compile distribution data for ladybird species throughout Europe, and use this to assess changes in distribution over time; 2. connect and engage people in nature and increase awareness about the diversity and ecological importance of ladybirds. In developing the application we first constructed a database including ladybird species from the UK, Czech Republic, Slovakia, Italy, Belgium and Portugal with associated information on relevant morphological features (e.g. size, main colour, pronotum pattern) to inform identification. Additionally, the species were assessed on the basis of probability of occurrence within each country which enables users to reduce the number of species to only those with relevance to the location of the recorder. This is amongst the first collaborative citizen science approaches aimed at involving participants across Europe in recording a group of insects. In the near future, we aim to expand the use of the application to all countries in Europe.